2018
DOI: 10.3389/fnins.2018.00929
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Neuroprotection of Electroacupuncture Therapy for Ischemic Stroke

Abstract: Stroke is one of the main causes of death all over the world. As the combination of acupuncture and electric stimulation, electroacupuncutre is a safe and effective therapy, which is commonly applied in ischemic stroke therapy in both experimental studies and clinical settings. The review was performed via searching for related articles in the databases of OVID, PUBMED, and ISI Web of Science from their respective inceptions to May 2018. In this review, we summarized the mechanism of EA for ischemic stroke via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 100 publications
2
52
0
Order By: Relevance
“…Cannabinoid receptors are expressed in brain tissue, and activation of these receptors give rise to neuroprotection against brain IRI. In our previous studies, we found that activation of the CB1 cannabinoid receptor by ACEA decreased brain IRI by restoring mitochondrial functions, and inhibition of mitochondrial permeability transition pore (MPTP) opening may be involved in the neuroprotective effects of ACEA 3,25 . Since the opening of the MPTP and subsequent mitochondrial swelling and enlargement lead to mitochondrial fission, we hypothesized that ACEA protects neuronal function in brain IRI by regulating mitochondrial fission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabinoid receptors are expressed in brain tissue, and activation of these receptors give rise to neuroprotection against brain IRI. In our previous studies, we found that activation of the CB1 cannabinoid receptor by ACEA decreased brain IRI by restoring mitochondrial functions, and inhibition of mitochondrial permeability transition pore (MPTP) opening may be involved in the neuroprotective effects of ACEA 3,25 . Since the opening of the MPTP and subsequent mitochondrial swelling and enlargement lead to mitochondrial fission, we hypothesized that ACEA protects neuronal function in brain IRI by regulating mitochondrial fission.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were plated into a 24-well cell culture plate. After the treatments, the supernatant of each well was collected, and the LDH activity in the supernatant was determined by using an LDH reagent kit as previously described 3 .…”
Section: Cell Viability and Ldh Release Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous studies, EA can improve neurological dysfunction, decrease the infarct volumes, and decrease the number of ischemic lesions (Xing et al, 2018a,b). Moreover, EA treatment could generate neuro regenerative effects for ischemic stroke, including promoting brain blood flow, regulating oxidative stress, reducing excitatory amino acids with neurotoxicity, maintaining the integrity of the blood-brain barrier, inhibiting neuronal apoptosis, increasing neurotrophic factors and producing brain ischemic tolerance (Xing et al, 2018c). Therefore, early intervention with EA in the acute stage of ischemic stroke has very important clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture helps harmonize Yin and Yang, then clearing blocked channels of Qi and Blood in the body so as to restore the normal body state, thus reducing motor impairment. A number of previous clinical trials have demonstrated the efficacy of acupuncture as a post-stroke intervention [9][10][11].…”
mentioning
confidence: 99%